Determination of Uric Acid in Biological Fluids by Ceria Nanoparticles Doped Reduced Graphene Oxide Nanocomposite Voltammetric Sensor. Issue 12 (30th December 2021) - Deng, Peihong; Feng, Jinxia; Xiao, Jingyun; Wei, Yanping; Zuo, Jinsong; Li, Junhua; Ding, Jianhua; He, Quanguo
Abstract : High levels of uric acid (UA) in the human body usually cause diabetes, hypertension and atherosclerosis, kidney diseases, and neurological diseases. Hence, it is important to develop sensitive methods for UA determination. In this paper, nanocomposite composed of ceria nanoparticles and reduced graphene was successfully modified on the surface of glassy carbon electrode (ceria NPs-rGO/GCE) by a simple electroreduction method. The morphology, structure and property of the ceria NPs-rGO/GCE was characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV). The electrocatalytic activity of the ceria NPs-rGO/GCE for uric acid (UA) oxidation was studied in detail. The results showed that the ceria NPs-rGO/GCE exhibited excellent selectivity and high sensitivity for UA detection. In 0.05 M H2 SO4 solution, a linear range of 0.02–20 μ M and a low detection limit of 8.0 nM of UA were obtained on the ceria NPs-rGO/GCE. This developed method was successfully applied for the detection of UA in human serum and urine samples, and its recoveries reached 95.8%-105.0%.